The Invisible Sand: Unpacking Metabolic Flows and Earthly Entanglements in Extended Urbanization - Lund Hansen, Anders ; 0000-0003-0245-6928; Barbesgaard, Mads; Côte, Muriel; Fabian, Louise; Mahmoud, Yahia; Ramasar, Vasna (Rethinking Marxism, 2025)
This article exposes the invisible sand that underpins Copenhagen’s transformation from fishing village to global city. By “following sand,” we trace how planetary material flows sustain urban expansion while entangling the city in processes of capital accumulation, class restructuring, and ecological degradation. Drawing on Science and Technology Studies (STS) approaches, yet situating them firmly within a Marxian political ecology, we foreground how sand functions as both resource and agent—at once enabling urban development and voicing ecological distress through disrupted habitats and contested territorialities. Case studies of Nordhavn and Lynetteholmen illustrate how urban growth in Copenhagen prioritizes potential rent over potential lives (Clark & Pissin 2020), privileging speculative land valorization over ecological survival and social rights. In bringing the “invisible hand” of political economy into dialogue with the “inviseble sand” of urban development, the article unpacks the metabolic flows and earthly entanglements of extended urbanization. In doing so, it advances a critical contribution to Marxist inquiry: exposing the socio-ecological destructions behind capital’s search for “free gifts” from nature (Harvey 1982, 2017), while opening imaginative space for rethinking urban futures grounded in care, community, and conviviality.